SUFFIXES -IE AND -Y IN MODIFYING COMMON FIRST NAMES - Alfonsa Vina Kanasya; Barli Bram (JOURNAL OF LANGUAGE, 2022)
The use of suffixes in the English language shows various functions, and one of them is endearment that happens especially in common first names or the way one addresses other people. This study aims to analyze the use of the suffix –ie and -y and to show endearment, especially in common first names and other possible words that also indicate endearment. This is a qualitative study that uses document analysis. The main data came from a list of common names as seen in Oxford Advanced Learner’s Dictionary 7th edition. Some additional data are also included, which are common names that are not listed in the dictionary. An additional observation was done to find adjectives-turn-nouns that are modified using suffixes -ie and -y that causes their category change. The research result shows that most of the nicknames usually come from either the first syllable of the name or the second or third syllable, and then those are modified using the suffix to create nicknames.